Phosphoinositide 3-kinase alterations in the thyroid gland – a review study - Wojciechowska-Durczyńska, Katarzyna; Lewiński, Andrzej (Archives of Medical Science, 2009)
The phosphoinositide 3-kinase (PI3K) pathway has become a subject of great interest of researchers in biomedicine worldwide. Recent studies have shown that PI3K plays a crucial role in various cellular functions: cell cycle progression, cell survival, adhesion and motility, angiogenesis, glucose homeostasis, cell size and organ size control. The phosphoinositide 3-kinase pathway alterations (PIK3CA gene mutations and/or amplification) have been observed in various human tumours. In the majority of diagnosed cases, mutations are localized in one of the three “hot spots” in the gene, responsible for coding catalytic subunit a of class I PI3K (PIK3CA). Mutations in PIK3CA were confirmed in breast, colon and endometrial cancers, while mutations and amplification of the PI3KCA gene are characteristic for thyroid cancer, as well. It results in increased activity of serine-threonine kinase (Akt), followed by excessive activation of cellular functions, uncontrolled proliferation and carcinogenesis.